Knowledge, Attitude, and Practices Associated with COVID-19 Among School Students in Bharatpur, Chitwan District of Nepal - Subedi, Deepak; Bhandari, Suman; Gaire, Asmita; Kandel, Milan; Subedi, Sanju; Karki, Surendra (International Journal of Medical Students, 2020)
Background: The virus causing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has reached pandemic proportions. Understanding people’s perceptions of the disease will provide tools to improve strategies to limit its transmission. This study aims to assess the knowledge, attitude, and practices (KAP) associated with the disease among high school students. Methods: Cross-sectional study conducted among secondary level students (grade 8th and 9th) in an urban high-school at Bharatpur, Chitwan, Nepal to assess KAP using a pre-tested questionnaire. Data were analyzed using Epi Info 7.2.3.1. Results: We collected 101 surveys (response rate 100%). Most of the students were found to be knowledgeable about the timeline of the first outbreak (92.08%), and nearly three-fourths of participants knew about hand-washing for 20 seconds (73.27%). Information about the presence of the disease in Nepal (50.50%), its causative agent (65.53%), and symptoms (57.43%) showed that there is a knowledge gap among participants. Most of the participants were found to have a positive attitude towards the prevention and control of the disease. The majority of the respondents reported using face mask (77.23%) and adopting hand-washing measures (79.21%) as preventive strategies. The majority of the students were highly concerned about the disease. Conclusion: Secondary level students of Chitwan, Nepal were found to have fair knowledge and understanding of the disease, showed a moderately positive attitude towards preventive measures, and reported appropriate preventive practices against the disease. It is recommended that a similar study with a wider population be conducted to assess KAP of Nepalese people towards SARS-CoV-2.